2018
DOI: 10.3390/molecules23092362
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hydroxy- and Epoxy-cis-Jasmone and Dihydrojasmone Derivatives Affect the Foraging Activity of the Peach Potato Aphid Myzus persicae (Sulzer) (Homoptera: Aphididae)

Abstract: Jasmonates show great potential in sustainable agriculture due to their various roles in natural mechanisms of plant defense, and because they are non-toxic, non-mutagenic, and easily metabolized. The aim of the study was to explore structure–activity relationships of dihydrojasmone, cis-jasmone, and their derivatives at the plant–aphid interface. We focused on the behavioral responses of aphids, following the exogenous application of natural jasmonates and their derivatives to the host plants. Aphid probing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 50 publications
(75 reference statements)
1
26
0
Order By: Relevance
“…Under natural conditions, the high proportion of salivation during the consumption of the phloem sap is typical for aphid behavior on unsuitable or non-host plants [51][52][53]. Similar effects on aphid behavior during the phloem phase were revealed when aphids were offered plants treated with natural and synthetic compounds, e.g., piperitone-derived lactones, cis-jasmone and its derivatives, β-thujone and its derivatives, or farnesol and nerolidol [32,[54][55][56]. The settling deterrent activities of β,γ-dimethyllactone (4) and α,γ-dimethylenelactone (7) were probably due to the post-ingestive inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…Under natural conditions, the high proportion of salivation during the consumption of the phloem sap is typical for aphid behavior on unsuitable or non-host plants [51][52][53]. Similar effects on aphid behavior during the phloem phase were revealed when aphids were offered plants treated with natural and synthetic compounds, e.g., piperitone-derived lactones, cis-jasmone and its derivatives, β-thujone and its derivatives, or farnesol and nerolidol [32,[54][55][56]. The settling deterrent activities of β,γ-dimethyllactone (4) and α,γ-dimethylenelactone (7) were probably due to the post-ingestive inhibition.…”
Section: Discussionmentioning
confidence: 86%
“…Third, +E aphids salivated longer in the phloem before the first E2 on +PGPR plants. Because various jasmonate components can be detected in the phloem and influence aphid feeding behavior [65], it seems that +E aphids were able to recognize the primed state of V. faba once it reached the phloem sap, and to adapt, in consequence, its salivation behavior. In A. pisum, some salivary proteins were identified as effectors that modulate insect feeding and survival on V. faba [66,67], and potentially inhibit plant immune responses in phloem sieve elements [64,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…We have established that the potency and persistence of behavioral effects on aphid probing of piperitone-, β -damascone-, xanthohumol-, isoxanthohumol-, and cis -jasmone-derived compounds depended on their substituents. Certain modifications caused shifts from attractant to deterrent properties, or vice versa [ 24 , 25 , 26 , 29 ]. In the present study, we also revealed specific structure–activity relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the synthesis of natural compound analogues is one of the most promising ways leading to their practical use in insect pest population control [ 24 ]. Structural transformations of the natural molecule usually change the mode of action and potency of its activity [ 25 , 26 ]. The possibility of reducing aphid infestation of crop plants by naringenin and its analogues application has never been explored.…”
Section: Introductionmentioning
confidence: 99%